Malolactic fermentation by Streptoccocus mutans and protection against oxidative damage - Mai Phuong, Nguyen Thi; E. MARQUIS, ROBERT (Academia Journal of Biology, 2012)
Streptococcus mutans is the primary etiological agent of human dental caries. The extraordinary ability of S. mutans to adapt and survive the environmental stresses in human mouth, particularly oxidative stress even though it does not have catalase, a key protective enzyme against oxidative damage, make it be an attractive subject for dental research. In the oral cavity, S. mutans is routinely exposed to reactive oxygen species (ROS) such as hydrogen peroxide (H2O2), superoxide (O2·-) and hydroxyl radical (OH·) generated by aerobic respiration, by H2O2 net secretors in plaque dental such as Streptococcus sanguis and S. gordonii, or by exposure to H2O2-containing dental care products. Alkali production by oral streptococci is considered important for dental plaque ecology and caries moderation. Recently, malolactic fermentation (MLF) was identified as a major system for alkali production by oral streptococci, including Streptococcus mutans. Malolactic fermentation is inducible by L-malate, involving decarboxylation of L-malate to yield L-lactic acid and concomitant reduction in acidity. Our major objectives in the work described in this paper were to further define the physiology of MLF of S. mutans and its roles in protection against oxidative stress damage. For the first time, L-malic, was found to enhance the protection of S. mutans against oxidative damage by reactive oxygen species including O2·- generated by xanthine-xanthine oxidase system; H2O2 and OH· produced via Fenton reaction between H2O2 and metal cations at pH values of 4.0. Protection involved L-malic uptake with the significantly enhanced production of ATP from malate fermentation, to maintain ATP pool levels for physiological activities in the cells. In general, oxidative protection by malolactic fermentation against ROS damage involving catabolism of L-malic and ATP production is likely to be an important virulent trait of S. mutans.